Efektifitas Pembiayaan Qarḍul Ḥasan Bagi Perkembangan Usaha Mikro Pada Baitul Maal Al-Amin, Kedungkandang, Kota Malang - Alficha Roby Vabella; Rahmad Hakim; Fien Zulkarijah (University of Darussalam Gontor, 2018)
This study aims to analyze two things: first, the effectiveness of qarḍul ḥasan financing in Baitul Maal Al-Amin at Kedungkandang for Micro, Small and Medium Business Development (known as UMKM). Second, to know the impact of qardhul hasan financing for micro business development at Kedungkandang. This research using case study approach with the method of data collection is an interview, observation and documentation. While data analysis is qualitative data analysis technique using Miles and Huberman’s model. The results of this study indicate that qarḍul ḥasan financing in Baitul Maal Al-Amin at Kedungkandang is quite effective with the fulfillment of measurement of several indicators such as usability, accuracy and objectivity, scope, accountability, cost effectiveness, and timeliness. In addition, qarḍul ḥasan financing in Baitul Maal Al-Amin has a significant impact for micro business development at Kedungkandang with the growth of sales turnover which is seen from the income and the growth of custome, even though the growth of local labor and the expansion of the place are has low significant impact.